1994
DOI: 10.1111/j.1570-7458.1994.tb01837.x
|View full text |Cite
|
Sign up to set email alerts
|

Disrupting spring colonization of Colorado potato beetle to nonrotated potato fields

Abstract: Overwintering Colorado potato beeries (Leptinotarsa decemlineata (Say)) were concentrated primarily within woody borders, and mortality was lower in borders than in potato fields. After overwintering, only 15-44% of live beetles were in the potato fields. In experiments with small plots, colonization of fields from woody borders was reduced ,,~ 60% by a trap crop, either treated with adulticide or with beetles collected daily. Such trap crops, or simply pitfall traps to prevent colonization from woody borders,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…CPB is a major pest of Solanaceous crops, such as potato ( Solanum tuberosum ), tomato ( S. lycopersicum ), and eggplant ( S. melongena )13. CPB originated in southern Mexico where the major host plants are buffalobur ( Solanum rostratum ) and S.angustifolium 14.…”
mentioning
confidence: 99%
“…CPB is a major pest of Solanaceous crops, such as potato ( Solanum tuberosum ), tomato ( S. lycopersicum ), and eggplant ( S. melongena )13. CPB originated in southern Mexico where the major host plants are buffalobur ( Solanum rostratum ) and S.angustifolium 14.…”
mentioning
confidence: 99%
“…Insects of this sort, such as the CPB are conducive to trapping in trenches. Weber et al (1994) found in Massachusetts that CPB could be found in over-wintering sites in densities as high as 188 adults/m 2 • Special in-ground plastic trenches have been designed for Canada and northeastern USA to trap these migrating adults (Boiteau et al 1994). The trench, a 25-cm-deep furrow lined with black plastic, can be dug around the potato field to be protected.…”
Section: Trenchmentioning
confidence: 99%
“…In Wisconsin, crop rotation within the pivot irrigation system provides a perfect situation for edge colonization (Hoy et al 1996). In Massachusetts (Weber et al 1994, Ferro 1995, attempts to control the beetle as they colonized the edge had only moderate results, suggesting that the beetles have a low residency time at the edge. In New Brunswick, border colonization occurs, but its frequency is unknown.…”
mentioning
confidence: 98%